1999
DOI: 10.1074/jbc.274.13.8865
|View full text |Cite
|
Sign up to set email alerts
|

ErbB-2 Amplification Inhibits Down-regulation and Induces Constitutive Activation of Both ErbB-2 and Epidermal Growth Factor Receptors

Abstract: ErbB-2/HER2 is an important signaling partner for the epidermal growth factor receptor (EGFR). Overexpression of erbB-2 is also associated with poor prognosis in breast cancer. To investigate how erbB-2 amplification affects its interactions with the EGFR, we used a human mammary epithelial cell system in which erbB-2 expression was increased 7-20-fold by gene transfection. We found that amplification of erbB-2 caused constitutive activation of erbB-2 as well as ligand-independent activation of the EGFR. Overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
225
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(245 citation statements)
references
References 46 publications
17
225
0
3
Order By: Relevance
“…Moreover, heterodimerization with or overexpression of HER2 may potentiate EGFR functioning by increasing EGF-binding affinity, stabilizing EGFR, promoting rapid recycling of EGFR back to the cell surface, and expanding the repertoire of receptor-associated substrates and signaling responses. 43,44 Furthermore, EGFR can 'crosstalk' with additional heterologous receptors activated by a variety of stimuli to amplify its biological activities. 40 In general, EGFR overexpression has been found to be associated with advanced tumor stage and poor prognosis in a number of human malignancies, such as carcinomas of the esophagus, 6 stomach, 45 colorectum, 16,46 bladder, 11 and breast.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, heterodimerization with or overexpression of HER2 may potentiate EGFR functioning by increasing EGF-binding affinity, stabilizing EGFR, promoting rapid recycling of EGFR back to the cell surface, and expanding the repertoire of receptor-associated substrates and signaling responses. 43,44 Furthermore, EGFR can 'crosstalk' with additional heterologous receptors activated by a variety of stimuli to amplify its biological activities. 40 In general, EGFR overexpression has been found to be associated with advanced tumor stage and poor prognosis in a number of human malignancies, such as carcinomas of the esophagus, 6 stomach, 45 colorectum, 16,46 bladder, 11 and breast.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor tyrosine kinase ErbB2 is a potent oncoprotein, and a high ErbB2 level can by itself activate ErbB receptors (Worthylake et al, 1999). Concordantly, increased ErbB2 levels can be found in several cancers (Klapper et al, 2000;Yarden, 2001), and high ErbB2 levels are correlated to a worse prognosis for breast cancer patients (Slamon et al, 1987;Hynes and Stern, 1994;De Placido et al, 1998;Pegram et al, 1998).…”
Section: Introductionmentioning
confidence: 90%
“…Little attention has been paid to the role of ErbB2 degradation in cancers, although when compromised it also would lead to increased ErbB2 levels and activity. Several studies have shown that endocytic downregulation of ErbB2 is impaired in cancer cells (Sorkin et al, 1993; Baulida et al, 1996;Wang et al, 1999;Hommelgaard et al, 2004;Austin et al, 2004;Longva et al, 2005), and ErbB2 can even transmit this property to the related epidermal growth factor receptor (EGFR; Muthuswamy et al, 1999;Wang et al, 1999;Worthylake et al, 1999;Haslekas et al, 2005). Inhibition of HSP90 (e.g., with geldanamycin [GA]) leads to increased internalization and lysosomal degradation of ErbB2 in a manner depending on proteasomal activity (Tikhomirov and Carpenter, 2000;Austin et al, 2004;Lerdrup et al, 2006).…”
mentioning
confidence: 99%
“…Stimulation of cells with EGF induces the heterodimerization of EGFR with other family members (Alroy and Yarden, 1997). It has been shown that the heterodimerization of EGFR with ErbB2 and ErbB3 inhibits the down-regulation of EGFR (Lenferink et al, 1998;Wang et al, 1999;Worthylake et al, 1999). Therefore, it is possible that UBPY also indirectly regulates the down-regulation of EGFR by controlling the cellular levels of its heterodimerization partners, ErbB2 and/or ErbB3.…”
Section: Role Of Ubpy In Egfr Down-regulationmentioning
confidence: 99%